Left atrial strain: a multi-modality, multi-vendor comparison study - Pathan, Faraz; Zainal Abidin, Hafisyatul Aiza; Vo, Quang Ha; Zhou, Hui; D'Angelo, Tommaso; Elen, Elen; Negishi, Kazuaki; Puntmann, Valentina O; Marwick, Thomas H; Nagel, Eike (European heart journal cardiovascular imaging, 2021)
Left atrial (LA) strain is a prognostic biomarker with utility across a spectrum of acute and chronic cardiovascular pathologies. There are limited data on intervendor differences and no data on intermodality differences for LA strain. We sought to compare the intervendor and intermodality differences between transthoracic echocardiography (TTE) and cardiac magnetic resonance (CMR) derived LA strain. We hypothesized that various components of atrial strain would show good intervendor and intermodality correlation but that there would be systematic differences between vendors and modalities. We evaluated 54 subjects (43 patients with a clinical indication for CMR and 11 healthy volunteers) in a study comparing TTE- and CMR-derived LA reservoir strain (ƐR), conduit strain (ƐCD), and contractile strain (ƐCT). The LA strain components were evaluated using four dedicated types of post-processing software. We evaluated the correlation and systematic bias between modalities and within each modality. Intervendor and intermodality correlation was: ƐR [intraclass correlation coefficient (ICC 0.64-0.90)], ƐCD (ICC 0.62-0.89), and ƐCT (ICC 0.58-0.77). There was evidence of systematic bias between vendors and modalities with mean differences ranging from (3.1-12.2%) for ƐR, ƐCD (1.6-8.6%), and ƐCT (0.3-3.6%). Reproducibility analysis revealed intraobserver coefficient of variance (COV) of 6.5-14.6% and interobserver COV of 9.9-18.7%. Vendor derived ƐR, ƐCD, and ƐCT demonstrates modest to excellent intervendor and intermodality correlation depending on strain component examined. There are systematic differences in measurements depending on modality and vendor. These differences may be addressed by future studies, which, examine calibration of LA geometry/higher frame rate imaging, semi-quantitative approaches, and improvements in reproducibility.